The culture of design - Julier, Guy (SAGE, 2013)
Just as the domains of design studies and practice are in a constant state of evolution, this edition has evolved to present a comprehensive discussion of contemporary design as a socio-technical cultural phenomenon in theory and practice. This text remains the only historically situated yet comprehensively contemporary account of how design as a creative industry materializes values into everyday lifestyles. The author has extended his framework to cover the large and diverse changes design has undergone in relation to digital economies and the rise of design thinking and social design.